Accounting and Tax Model for UMKM as Individual Taxpayers based on SAK EMKM and PP No 55 of 2022 Concerning Adjustments to Arrangements in the Field of Income Tax - Heidy Pesik; Anita Ludia Vivian Wauran; Jeffry Otniel Rengku; Johannes Kristoffel Santie; Anneke Marie Kaunang; Treesje Amelia Clara Langi; Nixon Sondakh (Future Science, 2023)
The existence of tax regulations in the field of income tax results in changes to the tax obligations of individual MSME business actors in the tax obligation mechanism, especially in determining the tax base for determining the tax payable, as regulated in Government Regulation No. 50 of 2022 concerning adjustments to regulations in the field of taxation which regulate income. taxable up to a turnover of IDR 500,000,000 for individual taxpayers as well as MSME entities.Where this regulation will be implemented starting January 1 2022, so the need for an accounting and tax model is really needed by MSME business actors in carrying out their tax obligations in accordance with the current regulations. Where as a basis for reporting tax obligations, an accounting report is needed as the basis for calculating tax obligations.This research aims to produce an Accounting Report design model based on Accounting Standards for Small and Medium Enterprise Entities (MSMEs) as taxpayers as well as a Tax report model that is in line with Government Regulation Number 55 of 2022 concerning adjustments to Regulations in the Income Tax Sector which are derived from the regulations of Law No. 7 in 2021 regarding the harmonization of tax regulations, in order to assist MSMEs in carrying out their tax obligations. The final result of this research is to produce an accounting and tax model that is in accordance with the EMKM regulations and PP No. 55 of 2022.